Osmium isotopes fingerprint mantle controls on the genesis of an epithermal gold province - Tassara, Santiago (2022)
The formation of crustal blocks enriched with gold (Au) deposits above subduction zones is intimately bound to the genesis and evolution of magmatic-hydrothermal systems. A longstanding question, however, is whether the metal fertility of these systems stems from distinct sources that are anomalously enriched in Au or from subsequent processes occurring during crustal magma emplacement and hydrothermal activity. The Deseado Massif auriferous province in southern Patagonia (Argentina) is a unique place to test these contrasting hypotheses because Au-bearing mantle xenoliths indicate the presence of an underlying Au-rich lithospheric mantle reservoir. However, direct geochemical links between the Au-rich mantle source and the formation of the Deseado Massif auriferous province in the overlying crust remain to be established. To address this prominent gap in knowledge, we used sulfide Re-Os geochronology to identify the source of Au at Cerro Vanguardia, the largest low-sulfidation epithermal Au-Ag deposit in the Deseado Massif. Pyrite from high-grade Au quartz veins yielded an isochron age of 147.4 ± 2.9 Ma (mean square of weighted deviates = 1.04, n = 8) and an initial 187Os/188Os ratio of 0.26 ± 0.01, fingerprinting a dominant mantle control for the source of Os and, by inference, the source of Au. Our data provide a unique geochemical linkage between an Au-rich subcontinental lithospheric mantle source and the genesis of epithermal Au deposits, supporting the hypothesis that pre-enriched mantle domains may be a critical factor underpinning the global-scale localization of Au provinces.